2017
DOI: 10.1038/pr.2017.53
|View full text |Cite
|
Sign up to set email alerts
|

Low birth weight is associated with impaired murine kidney development and function

Abstract: BACKGROUND: Low birth weight (LBW) neonates have impaired kidney development that leaves them susceptible to kidney disease and hypertension during adulthood. The study here identifies events that blunt nephrogenesis and kidney development in the murine LBW neonate. METHODS: We examined survival, kidney development, GFR, gene expression, and cyto-/chemokines in the LBW offspring of malnourished (caloric and protein-restricted) pregnant mice. RESULTS: Malnourished pregnant mothers gave birth to LBW neonates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Although cardiovascular and renal disease may arise via several mechanisms, increasing evidence from human and animal studies implicates low nephron number as being central to the disease process (Douglas‐Denton, McNamara, Hoy, Hughson, & Bertram, 2006; Hoy, Hughson, Singh, Douglas‐Denton, & Bertram, 2006; Low Birth Weight and Nephron Number Working Group, 2017; Luyckx et al, 2013; Wang & Garrett, 2017). The number of nephrons in normal human kidneys is directly correlated with birth weight, with low birth weight a proxy marker of a sub‐optimal intrauterine environment (Barnett et al, 2017; Hughson et al, 2008; Hughson, Farris 3rd, Douglas‐Denton, Hoy, & Bertram, 2003; Lackland & Barker, 2009). Animal studies have shown that a maternal low protein (LP) diet, typically associated with low birth weight, results in offspring with 20–30% fewer nephrons than control kidneys (Boubred et al, 2016; Hoppe, Evans, Moritz, et al, 2007; Hoppe, Evans, Bertram, & Moritz, 2007; Langley & Jackson, 1994; Langley‐Evans, 1997; Langley‐Evans et al, 1999; McMullen & Langley‐Evans, 2005; Sahajpal & Ashton, 2003; Woods, Ingelfinger, Nyengaard, & Rasch, 2001; Woods, Weeks, & Rasch, 2004; Zimanyi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although cardiovascular and renal disease may arise via several mechanisms, increasing evidence from human and animal studies implicates low nephron number as being central to the disease process (Douglas‐Denton, McNamara, Hoy, Hughson, & Bertram, 2006; Hoy, Hughson, Singh, Douglas‐Denton, & Bertram, 2006; Low Birth Weight and Nephron Number Working Group, 2017; Luyckx et al, 2013; Wang & Garrett, 2017). The number of nephrons in normal human kidneys is directly correlated with birth weight, with low birth weight a proxy marker of a sub‐optimal intrauterine environment (Barnett et al, 2017; Hughson et al, 2008; Hughson, Farris 3rd, Douglas‐Denton, Hoy, & Bertram, 2003; Lackland & Barker, 2009). Animal studies have shown that a maternal low protein (LP) diet, typically associated with low birth weight, results in offspring with 20–30% fewer nephrons than control kidneys (Boubred et al, 2016; Hoppe, Evans, Moritz, et al, 2007; Hoppe, Evans, Bertram, & Moritz, 2007; Langley & Jackson, 1994; Langley‐Evans, 1997; Langley‐Evans et al, 1999; McMullen & Langley‐Evans, 2005; Sahajpal & Ashton, 2003; Woods, Ingelfinger, Nyengaard, & Rasch, 2001; Woods, Weeks, & Rasch, 2004; Zimanyi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, these changes occurred exclusively in three-month-old offspring after catch-up growth had occurred, suggesting that catch-up growth may be responsible for the observed cardiac deficits. Nephrogenesis and renal function are also impeded in IUGR offspring via reduced nephron endowment, making these offspring further susceptible to hypertension and chronic kidney disease [67]. Studies of maternal malnutrition have identified the protein fetuin-B as having a role in this process, leading to increased generation of ROS in the kidneys of low birth weight offspring [68].…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…There is variation in RBF results between different methods in adult mice. Data on the 1st weeks after birth are sparse, but Barnett et al (2017) showed a rapid increase in renal perfusion from PND 0 [70 laser Doppler flowmetry (LDF) arbitrary units] to PND 3 (180 LDF arbitrary units) and PND 7 (280 LDF arbitrary units) in CD-1 mice.…”
Section: Functional Developmentmentioning
confidence: 99%